Tổng hợp và khảo sát một số tính chất của N-(2-furyl metyl)chitosan - Huệ, Nguyễn Thị; Tâm, Khiếu Thị; Hồng Anh, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
N-(2-furylmethyl)chitosan was synthesized from chitosan and furfural through two steps. The first one is the reaction between chitosan and furfural to form N-(2-furfuryliden) chitosan, the following one is the reduction of the later by NaBH4. The structure of the reaction products were confirmed by IR, UVand NMR spectroscopic data. The swelling degree in water, in NaOH 0.1 N solution  and the adsorption capacity of N-(2-furylmethyl)chitosan for Cu(II) were studied.